THE EFFICIENCY OF TRANSFERRING ATTENTION-GETTING DEVICES FROM ENGLISH TO LATVIAN: A CASE STUDY IN TRANSLATING NEWSPAPER HEADLINES - Iļjina, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The present study aims to explore the effectiveness of translating newspaper headlines from English to Latvian. The present study examines the linguistic devices that are used in order to catch readers’ attention to the headlines in newspapers. The research focuses on the analysis of the techniques that are employed to maintain the linguistic and stylistic equivalence of the utterances in the source and the target languages. The method of discourse analysis is applied in the research. The study concludes that the languages may have similar linguistic techniques to create attractive headlines. Moreover, the contrastive analysis demonstrates the feasibility of rendering the source text attractiveness into the target language. The most difficult decisions to make deal with cultural references that remain attractive only in their original linguistic environment.